ANALISIS TEMPORAL TOTAL SUSPENDED SOLIDS PADA AIR LIMBAH PERTAMBANGAN BATUBARA - Rahmat Rizali; Rizmi Yunita; Yunandar Yunandar; Kissinger Kissinger (Universitas Lambung Mangkurat, 2026)
Coal mining activities can increase pollutant loads in mine wastewater, particularly Total Suspended Solids (TSS), which exhibit high temporal variability influenced by operational and environmental conditions. This study aims to analyze the temporal dynamics of TSS concentrations in coal mining wastewater treated by Settling Pond SP-A based on daily monitoring data collected throughout 2023. The analysis employed descriptive statistical methods and daily time-series evaluation of inlet and outlet TSS concentrations, along with the assessment of TSS concentration differences (ΔTSS) as an indicator of settling performance. The results indicate that inlet TSS concentrations were highly variable, with a mean value of 2,630.54 mg/L, a median of 1,530.00 mg/L, and a maximum concentration reaching 195,000 mg/L. In contrast, outlet TSS concentrations were relatively stable, with a mean of 59.52 mg/L, a median of 55.00 mg/L, and a maximum value of 198.00 mg/L. The 90th percentile (P90) of outlet TSS was 100.20 mg/L, indicating that most effluent concentrations remained below the applicable environmental quality standard. Daily temporal patterns showed that episodic spikes in inlet TSS were not fully transmitted to the outlet. Predominantly positive ΔTSS values suggest that Settling Pond SP-A effectively reduced and stabilized TSS concentrations at the daily operational scale.